Perbedaan Kemampuan Motorik Ibu dalam Mencegah Regurgitasi pada Bayi Usia 0- 3 bulan Sebelum dan Sesudah Pendidikan Kesehatan (Latihan) Menyendawakan - Triatmi Andri Yanuarini; Sumy Dwi Antono; Septia Wulandari (Akademi Keperawatan Dharma Husada Kediri, 2016)
According to the Indonesian Demographic and Health Survey (SDKI) in 2012, The infant mortality rate was 31,41 by 1,000 live births occured in the first month of life. Result of the interview on four people at work area Ngadiluwih public health center at Kediri Regency, indicating lack of knowladge and attitude towards regurgitation. Therefore, acces to health emphasis on nutritional conseling, how to be parents and accident prevention help reduce the infant mortality rate. The research was conducted on 23 June to 8 July 2014 aimed to determain Differences in motor skills in preventing regurgitation mothers to infants aged 0-3 months before and after health education (training) burping (analityc studies at work area Ngadiluwih public health center at Kediri Regency). Statistical analysis with the wilcoxon test found that the value of count equal to 5,301 > z table (1,96) then H0 is rejected and H1 is accepted which means there is the Differences in motor skills in preventing regurgitation mothers to infants aged 0-3 months before and after health education (training) burping (analityc studies at work area Ngadiluwih public health center at Kediri Regency). Keywords: Regurgitation, IMR, Suddent Infant Death Syndrom